Bondage : labor and rights in Eurasia from the sixteenth to the early twentieth centuries - Stanziani, Alessandro (2014)
For the first time, this book provides the global history of labor in Central Eurasia, Russia, Europe, and the Indian Ocean between the sixteenth and the twentieth centuries. It contests common views on free and unfree labor, and compares the latter to many Western countries where wage conditions resembled those of domestic servants. This gave rise to extreme forms of dependency in the colonies, not only under slavery, but also afterwards in form of indentured labor in the Indian Ocean and obligatory labor in Africa. Stanziani shows that unfree labor and forms of economic coercion were perfec.